HUBUNGAN PENGETAHUAN IBU TENTANG KANKER SERVIK DENGAN PEMERIKSAAN IVA DI PUSKESMAS HAMPARAN PERAK KABUPATEN DELI SERDANG 2017 - Sibero, Jitasari Tarigan; Hanum, Rina (JURNAL KESEHATAN ALMUSLIM, 2021)
Cervical cancer (cervix) is a frightening disease for all women. Cervical cancer is most commonly found in other gynecologic cancers, and is a leading cause of death for women in developing countries. The low willingness of the mother to perform IVA examination is suspected because of the low knowledge of cervical cancer so that the lack of desire to perform IVA examination. To know the relationship of mother knowledge about cervical cancer with IVA examination. This type of research is an analytical survey with cross sectional approach. The location of the research was conducted at Puskesmas Hamparan Perak Kabupaten Deli Serdang. The population was all mothers who came to visit Hamparan Perak Puskesmas as many as 120 respondents, sampling using accendatal sampling, amounted to 35responden. The data used are primary and secondary data and analyzed by using Chi-Square test. The study showed the most respondents were knowledgeable less and enough, respectively as many as 15 respondents (42.9%) and only 5 respondents (14.2%) are well knowledgeable about cervical cancer. For examination of IVA most of the mother did not check IVA as much as 20 respondents (57,1%) and that examined IVA counted 15 respondents (42,9%). While on statistical test by using Chi-Square test with 95% confidence level with α= 0,05 obtained Asymp 2 sig 0,000. Conclusion; There is a significant relationship between mother knowledge about cervical cancer with IVA examination.